Hajj across empires - Choudhury, Rishad, 1984. (Cambridge, United Kingdom)
xxi, 351, [2] sayfa
Keywords: “Rishad Choudhury presents a new history of imperial connections across the Indian Ocean from 1739 to 1857, a period that witnessed the decline and collapse of Mughal rule and the consolidation of British colonialism in South Asia. In this highly original and comprehensive study, he reveals how the hajj pilgrimage significantly transformed Muslim political culture and colonial attitudes towards it, creating new ideas of religion and rule. Examining links between the Indian Subcontinent and the Ottoman Middle East through multilingual sources – from first-hand accounts to administrative archives of hajj – Choudhury uncovers a striking array of pilgrims who leveraged their experiences and exchanges abroad to address the decline and decentralization of an Islamic old regime at home. Hajjis crucially mediated the birth of modern Muslim political traditions around South Asia. Hajj across Empires argues they did so by channeling inter-imperial crosscurrents to successive surges of imperial revolution and regional regime change“ --